Perlindungan Hukum Terhadap Pejabat Pembuat Akta Tanah Dalam Pembuatan Akta Otenti - Teresia Din; Lilik Mulyadi; Udin Narsudin (Jurnal Penelitian Hukum Legalitas, 2016)
A PPAT (Land Deed Official) as the public official is vestewith the specific authority to draw up a deed, where the said deed is based on the interest of the two parties with a number of regulatory provisions. The research method used in this research is a normative judicial one. As a normative judicial research, the approach method applied to discuss the problem of research is through approach of statute approach, conceptual approach (Analytical and Conceptual Approach), and Comparative Approach by using deductive and / or inductive reasoning to get and find objective truth. From the result of the study, it may be surmised that a specific act may be construed as a criminal offence based on the normative judgment of several decisions made by the judge(s).